A self-assembled protein β-helix as a self-contained biofunctional motif - Camilla Dondi; Javier Garcia-Ruiz; Erol Hasan; Stephanie Rey; James E. Noble; Alex Hoose; Andrea Briones; Ibolya E. Kepiro; Nilofar Faruqui; Purnank Aggarwal; Poonam Ghai; Michael Shaw; et al. (Nature Communications)
Abstract Nature constructs matter by employing protein folding motifs, many of which have been synthetically reconstituted to exploit function. A less understood motif whose structure-function relationships remain unexploited is formed by parallel β-strands arranged in a helical repetitive pattern, termed a β-helix. Herein we reconstitute a protein β-helix by design and endow it with biological function. Unlike β-helical proteins, which are contiguous covalent structures, this β-helix self-assembles from an elementary sequence of 18 amino acids. Using a combination of experimental and computational methods, we demonstrate that the resulting assemblies are discrete cylindrical structures exhibiting conserved dimensions at the nanoscale. We provide evidence for the structures to form a carpet-like three-dimensional scaffold promoting and inhibiting the growth of human and bacterial cells, respectively, while being able to mediate intracellular gene delivery. The study introduces a self-assembled β-helix as a self-contained bio- and multi-functional motif for exploring and exploiting mechanistic biology.